PENERAPAN MODEL PEMBELAJARAN PROJECT BASE LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR MATA KULIAH RIAS FANTASI DI AKS-AKK YOGYAKARTA - Enny Harwiyati; Helmia Cipta Rohmawati (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2022)
The purpose of the writing is to find out the application of the Project Base Learning learning model in improving the learning achievement of the Rias Fantasi course in students of the AKS